A FRESHMAN YEAR MATHEMATICS DISCIPLINE STUDENT OF A TEACHER TRAINING COURSE - HIS/HER WORRY AND EXPECTATION - DOFKOVA, Radka; FACEVICOVA, Kamila (Trends in education, 2017)
It is generally assumed that the quality of teachers, and thus also that of educational processes in schools is conditioned by the quality of the students that apply for teacher training courses. There are several common features characteristic for applicants in the Czech Republic that have been established in the long run: a vast majority among them are women; a significant part of the students see their studies at the teacher training faculty only as an alternative to their preferred field of study; attitudes of prospective teachers to their profession are differentiated (based on gender, etc.), and there are regional differences among the applicants. The above mentioned claims might be complemented with those that are frequently used about teacher training courses students: teacher training courses are only their second choice, without actually aspiring to become teachers by profession. Teacher training courses are generally considered as seemingly easier, a significant part of the students do not work as teachers after graduating from the school. The goal of this contribution is to describe the attitude of teacher training students to the study of mathematics directly after starting the teacher training courses. That is why we have shown here the results of a survey carried out among 134 freshman year students in the winter semester of the 2016/2017 academic year that filled out a questionnaire probing into the following aspects of their future profession.
Keywords: teacher; teaching; mathematics; prospective math teacher; teacher training faculty